(untitled) (International Journal of Engineering and Computer Science, 2016)
The Artificial Intelligence is the modern era technology which plays a vital role in the modern engineering by using which we can enhance the technology. It not only influence the technology but also it provides a wide range of sophisticated paths for the humans to put his thoughts in terms of machine intelligence. The major factor lies in the Human learning is the decision taking ability is poor. So we are moving towards the Machine and to make a machine more interactive, we think for intelligence.